Study of changes in serum sodium and potassium levels in term and preterm neonates following phototherapy - Annachira Chinnappa, Likitha; Rudrappa, Sudha (International Journal of Contemporary Pediatrics, 2022)
Background: Neonatal hyperbilirubinemia is a common physical finding in the first week of life. It is a common cause of hospital readmission during neonatal period. Phototherapy is an important treatment modality. However, it has some complications; amongst them serum electrolyte changes are a common complication. Objective of this study is to determine the changes in serum sodium and potassium in neonates before and after phototherapy and compare the occurrence of these changes in relation to gestational age and birth weight. Methods: In a prospective hospital based comparative study both term and preterm neonates admitted in neonatal intensive care unit receiving phototherapy at Cheluvamba hospital Mysore from July 2021 to April 2022 (10 months) were studied. A predesigned proforma aided the enrolment of new-borns into the study. Serum bilirubin and electrolytes and a comparative study was made between before and after phototherapy groups to determine the incidence of electrolyte imbalance. Results: The study group included 100 neonates. Incidence of low-birth-weight babies was 28% and preterm 22%. Mean birth weight and gestational age was 2.91±0.65 kg and 38.43±1.96 week respectively. The incidence of hyponatremia post phototherapy was found to be 9% which was more in low birth weight and preterm neonates (p<0.001) and was statistically significant. The incidence of potassium changes was found to be non-significant. Conclusions: The study shows that neonates under phototherapy are at higher risk of hyponatremia. This risk is greater in premature and low birth weight babies and hence this group of babies should be closely monitored for electrolyte changes and managed accordingly.